Jadilah Sesuai Maksud Allah Atasmu - Dick Eugenio (Sekolah Tinggi Theologia Nazarene Indonesia, 2021)
The relationship between the Christian and culture is the overarching theme in the Petrine epistles, making them relevant now as they were first penned. Both 1 and 2 Peter can be considered as “epistles of hope” with “the best commentaries on Matthew 5:10, ‘blessed are the persecuted because of righteousness…” This paper’s primary question is: “In calling his readers to be holy in all their conduct, what does Peter identify as help and hindrances?” The answers are discussions of identity: the “identity” of the One who elects, the present identity of the elected people, and the life that identifies them as elect in contrast to the identity of the non-elect. By admonishing his audience to consider these, Peter hopes that they will remain committed to their faith in the midst of persecution and challenges. Instead of despair and apostasy, Christians ought to remember their identity and calling as the chosen people of God.